Risk behaviors and well-being among Egyptian and Roma adolescents in Albania during the COVID-19 pandemic: Vulnerability and resilience in a positive youth development perspective - Miconi, Diana; Ouimet, Sonia; Kafi, Mohammed Abdullah Heel; Dervishi, Eglantina; Wiium, Nora; Rousseau, Cécile (Frontiers in Psychology, 2023)
Egyptian and Roma communities represent the most deprived and stigmatized ethnic minorities in Albania. However, research investigating vulnerability and well-being in youth from these communities is scant. Even less is known among Egyptian and Roma adolescents who dropped-out of school. Within a Positive Youth Development framework, we investigated among Egyptian and Roma adolescents during the COVID-19 pandemic: 1) risk behaviors and well-being; 2) available personal and contextual assets; 3) associations between personal and contextual assets, risk behaviors and well-being; 4) specificities by ethnicity, gender, and education. A total of 201 Egyptian and Roma adolescents (Mage = 16.63, SDage = 1.80; 47% girls; 53% dropped-out of school) completed a series of questionnaires in a community setting. Binomial, Poisson and linear regression models indicated that Egyptian and Roma adolescents reported similar and high levels of risk behaviors, with boys reporting overall more risk behaviors than girls. Low level of well-being and of personal and contextual assets were reported. Girls reported higher family assets, positive values and social competence than boys. The situation of adolescents attending school was overall no better than that of youth who had dropped out. Higher positive identity was associated with higher well-being. Intervention and prevention efforts are urgently needed to support minority adolescents’ development during and in the aftermath of the pandemic. They should address the structural factors which limit the availability of personal and contextual resources in minority youth’s lives. In particular, interventions aimed at building safer neighborhoods and schools for minority youth should be a priority.